1986
DOI: 10.1021/bi00359a018
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids decrease the synthesis of type I procollagen mRNAs

Abstract: Glucocorticoids selectively decrease procollagen synthesis in animal and human skin fibroblasts. beta-Actin content and beta-actin mRNA are not affected by glucocorticoid treatment of chick skin fibroblasts. The inhibitory effect of glucocorticoids on procollagen synthesis is associated with a decrease in total cellular type I procollagen mRNAs in chick skin fibroblasts. These effects of dexamethasone are receptor mediated as determined by pretreatment with the glucocorticoid antagonists progesterone and RU-48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 47 publications
(33 reference statements)
1
37
0
Order By: Relevance
“…In vitro experiments have demonstrated that DEX is able to reduce collagen synthesis by fibroblasts [30,31]. In line with this, DEX treatment has been demonstrated to decrease total body collagen synthesis in infants with CLD [9,32].…”
Section: Discussionmentioning
confidence: 86%
“…In vitro experiments have demonstrated that DEX is able to reduce collagen synthesis by fibroblasts [30,31]. In line with this, DEX treatment has been demonstrated to decrease total body collagen synthesis in infants with CLD [9,32].…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, glucocorticoids decrease transcription of the genes for proopiomelacortin in pituitary tumor cells (29), a1-fetoprotein in developing rat liver cells (30), type 1 procollagen in chicken skin fibroblasts (31), and collagenase in rabbit synovial cells (24). During the shutdown of transcription by glucocorticoid hormones, there is no demonstrably accelerated breakdown of nascent transcripts (24,30,31). In contrast, Dex does not influence transcription of f3-actin or FOS genes or the stability of the corresponding mRNAs in U-937 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic glucocorticoid dexamethasone was previously described to antagonize TGF-h effects, especially collagen inducing properties (Gras et al, 2001;Cockayne et al, 1986) and it was recently demonstrated in HSC that glucocorticoids reduce the bioavailability of TGF-h directly (Bolkenius et al, 2004).…”
Section: Introductionmentioning
confidence: 99%